Early Magnetic Resonance Imaging–Based Changes in Patients With Meniscal Tear and Osteoarthritis: Eighteen‐Month Data From a Randomized Controlled Trial of Arthroscopic Partial Meniscectomy Versus Physical Therapy. Issue 5 (28th April 2020) - Collins, Jamie E.; Losina, Elena; Marx, Robert G.; Guermazi, Ali; Jarraya, Mohamed; Jones, Morgan H.; Levy, Bruce A.; Mandl, Lisa A.; Martin, Scott D.; Wright, Rick W.; Spindler, Kurt P.; Katz, Jeffrey N.; et al.
Abstract : Objective: The present study was undertaken to evaluate changes in knee magnetic resonance imaging (MRI) findings over the course of 18 months in subjects with osteoarthritic change and meniscal tear treated with arthroscopic partial meniscectomy (APM) or nonoperatively with physical therapy (PT). Methods: We used 18‐month follow‐up data from the Meniscal Tear in Osteoarthritis Research Trial. MRI results were read with reference to the MRI Osteoarthritis Knee Score. We focused on 18‐month change in bone marrow lesions (BMLs), cartilage thickness, cartilage surface area, osteophyte size, effusion‐synovitis, and Hoffa‐synovitis. We used multinomial logistic regression to assess associations between MRI‐based changes in each feature and treatment type. Results: A total of 351 subjects were randomized, and 225 had both baseline and 18‐month MRI results. In both treatment groups, patients experienced substantial changes in several MRI‐based markers. In 60% of the APM group, versus 33% of the PT group, cartilage surface area damage advanced in ≥2 subregions (adjusted odds ratio 4.2 [95% confidence interval 2.0–9.0). Patients who underwent APM also had greater advancement in scores for osteophytes and effusion‐synovitis. We did not find significant associations between treatment type and change in cartilage thickness, BMLs, or Hoffa‐synovitis. Conclusion: This cohort of patients with meniscal tear and osteoarthritis showed marked advancement in MRI‐based features over 18 months. Patients treated with APM showed more advancement in some features compared to those treated nonoperatively. The clinical relevance of these early findings is unknown and requires further study.